Causal relationship between current account and financial account: the case of Tunisia. Issue 1 (2nd January 2020) - Farhoud, Hager; Taleb, Lotfi
ABSTRACT: The Tunisian economy during the last thirty years suffered from a chronic current account deficit. The present paper investigates the long and short-run dynamics between the surplus of the aggregated and disaggregated financial account and the persistent pattern of current account deficit in Tunisia over the period 1977–2009. Based on bounds testing cointegration approach using an autoregressive distributed lag (ARDL), we found evidence supportive of long-run cointegration relationships between the current account and the financial account for both aggregated and disaggregated levels. The results also highlight that there is evidence of unidirectional causality from portfolio investment to the current account over the long-run. These findings suggest that the current account should be used by the Tunisian government as a control variable for capital flows and could be considered as valuable information for the liberalization of the financial account in Tunisia.